Kesalahan Peserta Didik Kelas VIII MTs Modern Al-Rifa’ei dalam Menyelesaikan Soal Berbasis Etnomatematika dengan Konteks Masjid Kasunyatan Banten Menggunakan Teori Nolting - Masamah, Ulfa; Rakhmandani, Miranda Puja (Faculty of Teacher Training and Education, 2025)
Ethnomathematics links mathematical concepts with culture to create contextual and meaningful learning such as the application at the Kasunyatan Banten Mosque which has historical and cultural values. This study aims to analyze the errors of class VIII students of MTs Modern Al-Rifa'ei in solving ethnomathematics-based problems using six types of errors in accordance with Nolting's Theory. This study uses a qualitative approach with a case study type. The subjects of the study consisted of class VIII MTs totaling 6 subjects who experienced errors based on Nolting's Theory and on the recommendation of the teacher. Data collection techniques used tests and interviews. The test instrument adopted ethnomathematics-based essay questions from the Kasunyatan Banten Mosque. The credibility test used triangulation techniques, namely tests, interviews, and documentation. Data were analyzed using error indicators in Nolting's Theory. The results of this study indicate that the errors made by students are 1) Misread-direction errors in the form of information that is available and asked is not written; 2) Careless errors in the form of inconsistency in writing units and miscalculations; 3) Concept errors in the form of not understanding the concept of arithmetic operations, units and not finding a solution strategy; 4) Application errors, inaccuracy in determining formulas and applying them to different situations; 5) Test-taking errors, errors in making decisions due to incorrect formulas and questions; and 6) Study errors, not being used to solving story problems. These findings can be used as a basis for designing more effective ethnomathematics-based learning by identifying mathematical concepts that are difficult for students to understand and connecting them to relevant cultural contexts